Mitigating turnover intention among private school teachers - Moh. Alifuddin; W Widodo (Journal of Education and Learning (EduLearn), 2021)
This study explored the effect of compensation on teachers’ turnover intention mediated by organizational commitment. The research data was collected by a questionnaire through the survey methods toward 207 honorary teachers of a private school in Indonesia. Data analysis employed path analysis, supported by descriptive statistics and a correlational matrix. The result indicated that compensation significantly affects teachers’ turnover intention meditating by organizational commitment. This study also found a fit research model that can discuss among researchers and practitioners as references/discourse or a strategy for mitigating turnover intention in various contexts and research fields.